2017
DOI: 10.1016/j.measurement.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating multi-GNSS performance in the UK and China based on a zero-baseline measurement approach

Abstract: GPS is the positioning tool of choice for a wide variety of applications where accurate (cm level or less) positions are required. However GPS is susceptible to a variety of errors that degrade both the quality of the position solution and the availability of these solutions.The contribution of additional observations from other GNSS systems may improve the quality of the positioning solution. This study investigates the contribution of the GLONASS and BeiDou systems and the potential improvement to the precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Numerous investigations have demonstrated that a multi-GNSS approach (e.g., GPS + BeiDou) is able to improve the performance of real-time-kinematic (RTK) positioning, particularly in urban and mountainous areas, where the lack of visible GPS satellite numbers and multipath reflections limit the performance of RTK [55][56][57][58][59]. However, it has been reported that multi-GNSS observations do not noticeably improve the accuracy of static positioning compared to GPS-only observations; somehow, using multi-GNSS observations can even degrade the accuracy of static positioning compared to using GPS-only observations [60][61][62]. Accordingly, we processed GPS and BeiDou observations separately in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations have demonstrated that a multi-GNSS approach (e.g., GPS + BeiDou) is able to improve the performance of real-time-kinematic (RTK) positioning, particularly in urban and mountainous areas, where the lack of visible GPS satellite numbers and multipath reflections limit the performance of RTK [55][56][57][58][59]. However, it has been reported that multi-GNSS observations do not noticeably improve the accuracy of static positioning compared to GPS-only observations; somehow, using multi-GNSS observations can even degrade the accuracy of static positioning compared to using GPS-only observations [60][61][62]. Accordingly, we processed GPS and BeiDou observations separately in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the potential for using the Global Positioning System (GPS) in structural health monitoring (SHM) has been revealed through experimental studies, which proved its ability in monitoring oscillations of subcentimeter level displacement and high‐rate frequencies,[] and applications to real monitoring of bridges[] and buildings or towers,[] where the GPS monitoring was successfully used to estimate the main characteristics of the structures response. Furthermore, the recent rapid developments in the GPS system, such as 100‐Hz high‐rate receivers,[] the precise point positioning (PPP) solution[] among others, and the contribution of other satellite navigation systems,[] resulting in the Global Navigation Satellite System (GNSS), have lead to further enhancement of the GPS/GNSS solution and increased reliability of the displacement time series. Thus, the potential of real‐time GPS/GNSS monitoring with even a few millimeter accuracy, in an independent coordinate system for short‐ or long‐period monitoring, makes GPS a useful tool for SHM.…”
Section: Introductionmentioning
confidence: 99%
“…Also, obstructions such as bridge cables and passing vehicles may significantly weaken the satellite geometry . Under circumstance of the weak satellite geometry, integrating GPS with other GNSS constellations is an ideal strategy . Further to the established GPS and GLONASS, BDS and Galileo positioning systems are expected to provide global services upon completion in 2020.…”
Section: Combination Of Gps and Other Gnss Constellationsmentioning
confidence: 99%